"Saying Nothing Is Saying Something": Affective Encounters with the Muslim Other in Amsterdam Public Transport. Issue 7 (10th November 2021) - Shaker, Reza
Abstract : Taking the Muslim other into consideration, this article investigates Muslims' everyday encounters within the (im)mobile spaces of public transport that entangle bodies with different histories, backgrounds, and imaginaries. Building on affective atmospheres, I propose an embodied understanding of othering practices and traveling with difference in public transport. Employing (auto)ethnography in Amsterdam, I present public transport as a cross-cultural meeting place with spatial negotiation of difference to study everyday travel experiences of young Muslims. Contributing to the field of mobilities studies, this article bridges the gap in the empirical evidence on the role of public transport, race, and religion in the othering of Muslims.